2006
DOI: 10.1002/pbc.20896
|View full text |Cite
|
Sign up to set email alerts
|

Pernicious anemia associated with autoimmune hemolytic anemia and alopecia areata

Abstract: We report a 16-year-old male with a combination of pernicious anemia, auto-immune hemolytic anemia and alopecia areata. Autoimmune hemolytic anemia coexisted with pernicious anemia but was diagnosed only when the anemia failed to respond to cobalamin therapy. Alopecia areata occurred 9 years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…AA has been associated with numerous comorbid immune-mediated diseases, and an association with PA would be reason for B 12 deficiency to be more prevalent in AA patients compared to controls. This principle is evidenced by a case-report [81] of a patient diagnosed with pernicious anemia at age 16 who later developed AA at age 24, and another report [73] of a patient who developed type 1 diabetes at age 18, 9 months later developed AA, and at age 27 was diagnosed with pernicious anemia. However, as mentioned previously, available case-control studies [72, 79, 80] with multiple AA cases did not identify any such differences in B 12 levels in patients compared to controls.…”
Section: Micronutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…AA has been associated with numerous comorbid immune-mediated diseases, and an association with PA would be reason for B 12 deficiency to be more prevalent in AA patients compared to controls. This principle is evidenced by a case-report [81] of a patient diagnosed with pernicious anemia at age 16 who later developed AA at age 24, and another report [73] of a patient who developed type 1 diabetes at age 18, 9 months later developed AA, and at age 27 was diagnosed with pernicious anemia. However, as mentioned previously, available case-control studies [72, 79, 80] with multiple AA cases did not identify any such differences in B 12 levels in patients compared to controls.…”
Section: Micronutrientsmentioning
confidence: 99%
“…At present, there are few studies (Table 5) [72, 73, 7881] assessing B vitamin status in patients with AA. Yousefi et al [78] found lower RBC folate levels in 29 Iranian AA patients compared to controls.…”
Section: Micronutrientsmentioning
confidence: 99%
“…6,7,17,18 In one case of AIHA and B12 deficiency, related to metaplastic atrophic gastritis, successful treatment was achieved with steroids and vitamin B12. 6 In two other papers, failure to respond to B12 supplementation highlighted the AIHA diagnosis and necessity of steroid treatment, 7,17 while another patient responded to B12 therapy without resorting to steroids. 18 In all the described cases, both anti-PCA and anti-InF antibodies were positive.…”
Section: Discussionmentioning
confidence: 99%
“…PA with positive DAT status is associated with the appearance of hemolysis [ 1 , 7 9 ]. The autoantibody produced in PA patients may usually have non-specific reaction with erythrocyte.…”
Section: Discussionmentioning
confidence: 99%
“…The autoantibody produced in PA patients may usually have non-specific reaction with erythrocyte. However, in some cases, autoantibody affects hemolytic reaction to erythrocyte [ 7 , 8 ]; in which anemia will be persist with Vit.B12 treatment itself. PA has the status of ineffective erythropoiesis, where most of erythroblasts are dying in the intramedullary area by apoptosis, and release LDH [ 10 ].…”
Section: Discussionmentioning
confidence: 99%